2021
DOI: 10.1177/21925682211003854
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors For Prolonged Opioid Use After Spine Surgery

Abstract: Study Design: Retrospective review. Objective: Our purpose was to evaluate factors associated with increased risk of prolonged post-operative opioid pain medication usage following spine surgery, as well as identify the risk of various post-operative complications that may be associated with pre-operative opioid usage. Methods: The MarketScan commercial claims and encounters database includes approximately 39 million patients per year. Patients undergoing cervical and lumbar spine surgery between the years 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 12 publications
2
34
0
Order By: Relevance
“…While there was overall a large reduction in patients on opioids postoperatively in the high and low opioid groups, this study also demonstrated that greater preoperative opioid use was associated with a significantly increased risk of postoperative use beyond the immediate postoperative period (90–455 days). These results align with prior literature which has demonstrated greater preoperative opioid use to be a significant predictor of decreased postoperative opioid independence following spine surgery ( 26 - 29 ). This association is not limited to spine surgery and has also been demonstrated in other types of orthopaedic surgery including elective total joint arthroplasty ( 30 ).…”
Section: Discussionsupporting
confidence: 90%
“…While there was overall a large reduction in patients on opioids postoperatively in the high and low opioid groups, this study also demonstrated that greater preoperative opioid use was associated with a significantly increased risk of postoperative use beyond the immediate postoperative period (90–455 days). These results align with prior literature which has demonstrated greater preoperative opioid use to be a significant predictor of decreased postoperative opioid independence following spine surgery ( 26 - 29 ). This association is not limited to spine surgery and has also been demonstrated in other types of orthopaedic surgery including elective total joint arthroplasty ( 30 ).…”
Section: Discussionsupporting
confidence: 90%
“…2,9,10 Approximately 9% of patients continue to use opioids one year after spine surgery. 11 Risk factors for persistent opioid use after spine surgery include preoperative opioid use, depression, anxiety, chronic pain diagnoses, use of non-opioid pain medications, lower socioeconomic status, and younger age. 11,12 Careful consideration of these patient-level characteristics is warranted when formulating a multimodal pain regimen prior to surgery.…”
Section: Opioid Managementmentioning
confidence: 99%
“…19 Studies have also found associations between preoperative opioid use and increased postoperative opioid quantity and duration of use after spine surgery. 18,20–22…”
Section: Discussionmentioning
confidence: 99%